Preservative treatment of rubberwood(Hevea brasiliensis) - Gnanaharan R; Mathew G (KFRI Research Report, 1982)
Susceptibility of rubber wood to fungal and insect attack limits its wider utilisation otherwise possible. The objective of this study was to increase the seervice life of rubber wood by introducing a cheap preservative into wood by diffusion process, employing a simple technique which can be carried out even in a small size saw-mill. Treatment with boron solutions of higher concentration resulted in higher loading of chemicals into wood. However, using solutions of higher concentration has some disadvantages. This study found that adequate loading of chemicals can be obtained by using solutions of lower concentration at ambient temperature. Immersing 25 mm thick thick material in a 10;boric acid equivalent (BAE) solution containing 0.5;sodium pentachlorophenoxide at ambient temperature for 40 minutes gave adequate loading of chemicals. It was found that increasing the immersion time does not increase the loading of chemicals appreciably. Rubber wood is very permeable and it does not pose any problem for the chemicals to diffuse into the wood. Treatment with boron chemicals to a loading of 0.4;BAE was found adequate to protect rubber wood against the insect borer Sinoxylon anale. Material treated by diffusion process will be suitable for making furniture, door and window frames, etc.
Keywords: Boron chemicals; Diddusion process; Rubberwood; Rubberwood preservation; Sapstain and mould fungi